THE CONTRIBUTION OF STUDENTSâ BELIEFS ABOUT LANGUAGE LEARNING, LEARNING STYLES, AND LANGUAGE LEARNING STRATEGIES TOWARD THE ENGLISH ACHIEVEMENT OF THE ELEVENTH GRADE STUDENTS OF STATE SENIOR HIGH SCHOOLS IN SINGARAJA - Angelianawati, L (Jurnal Pendidikan Bahasa, 2012)
Abstract This study was a correlational study, which was aimed at investigating whether or not there was a significant contribution of beliefs about language learning, learning styles, and language learning strategies on studentsâ English achievement. The research was done toward the eleventh grade students of state senior high schools in Singaraja Semester 1, in the academic year 2011/2012. The number of population was 798 students; and the sample was 160, which were determined through proportional random sampling technique. The data of beliefs about language learning were collected through BALLI (Horwitz, 1987) which was adapted from Artini (2006), learning styles through PLSPQ (Reid, 1984), language learning strategies through SILL (Oxford, 1990), and English achievement from documentations, namely from studentsâ school report books. The data were analyzed by using descriptive and inferential statistics. The descriptive statistics was used to describe the obtained variable data and the inferential statistics was used to analyze the requirement testing and hypothesis testing. The research results showed that there were significant contributions of each predictor, i.e. beliefs about language learning, learning styles, and language learning strategies, to the studentsâ English achievement (Ï < 0.05), namely 3.6% with r = 0.190, 5% with r = 0.224, and 2.9% with r = 0.172, correspondingly. There was also a positive and significant contribution of the beliefs about language learning, learning styles and language learning strategies simultaneously to their English achievement, with r = 0.257, Ï < 0.05, and the coefficient of determination (r 2) = 0.066 or 6.6%, in which the effective contribution of each from the strongest to the weakest were learning styles 3.51%, beliefs about language learning 1.71%, and language learning strategies 1.38% respectively. Key terms : beliefs about language learning, learning styles, language learning strategies, English achievement